MO189: The Clinical Relevance of Measured GFR in Patients with Solitary Kidney after Radical Nephrectomy: The Estimation is not Enough. (3rd May 2022) - Trevisani, Francesco; Quattrini, Giulia; Franchini, Melania; Bonzi, Camilla; Rita Rota, Maria; Cinque, Alessandra; Bettiga, Arianna; Capitanio, Umberto; Salonia, Andrea; Locatelli, Massimo; Pizzagalli, Giorgio; Montorsi, Francesco
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) represents the major postoperative long-term complication in patients who undergo radical nephrectomy (RN) for the presence of a renal mass. The development of a mild to severe grade of CKD can dramatically change the lifespan of this category of patients who can experience not only an augmented rate of cardiovascular diseases but also cancer recurrence and oncological therapies based on nephrotoxic agents. Therefore, preventive strategies for reducing the risk of CKD are strictly required. Among them, one of the most important tools is represented by the correct assessment of renal function. In fact, especially in the oncological scenario, there are various causes of factitious elevation or reduction of serum creatinine due to the frequent modification of body composition, measurement interference with the assay and altered tubular secretion. Nevertheless, the use of estimated GFR based on serum creatinine levels remains nowadays the most common method to define renal function in RN patients, both in the oncological and in the urological universe. The aim of this study was to determine the extent of the error of eGFR compared to the mGFR in a consecutive prospective cohort of RN patients who remained with a solitary kidney. METHOD: A total consecutive cohort of 115 RN patients enrolled in a single tertiary institution between 2018 and 2021 was collected in order to compare the most common eGFR formulas used by physicians (Cockroft-Gault, MDRD, CKD-EPI based on serum creatinine and/or serum cystatin and the new eGFR equation based on creatinine and cystatin without race adjustment) with the most widespread mGFR method (Iohexol Plasma Clearance). The mGFR technique together with the serum creatinine/cystatin measurement was performed after 12 months from the operation in order to consider a steady state for the chronic renal function. All clinical variables were reported for each pt. CKD classification was defined accorded to K-DIGO 2012 guidelines. The agreement between eGFR and mGFR was evaluated using bias (as median of difference), precision (as interquartile range of difference-IQR), accuracy (as P30) and total deviation index (TDI). The differences between cohorts were evaluated with Fisher's exact test and Chi-squared test for ordinal characteristics and Wilcoxon rank sum test for continuous variables. Data analysis was performed using programming language R and Python. RESULTS: Clinical data were as follows: median age 66 (IQR 27.66), M/F ratio 4.48, median BMI 24.6 (IQR: 0.003, 24.6). 51.3% of patients had hypertension, 10.4% were diabetics. The median creatinine level in the overall population was 1.49 mg/dL (IQR: 0.8, 1.49), the median cystatin level was 1.33 mg/dL (IQR: 0.55, 1.33). Based on iohexol plasma clearance, 0.87% patients were classified in CKD in stage 1, 17.39% in stage 2, 39.13% in stage 3a, 25.22% in stage 3b, 16.52% in stage 4 and 0.87% in stage 5. Surprisingly, a non-negligible error was reported in each CKD class with a huge discrepancy between the eGFR formulas and the gold standard method (Figures 1 and 2), suggesting the pivotal role of mGFR in the clinical decision-making algorithm for RN patients. CONCLUSION: In daily clinical practice, an appropriate nephrological tailored follow-up based on mGFR is mandatory for RN patients with a solitary kidney. In fact, a simple renal evaluation using eGFR can only increase the risk of clinical errors, sometimes underestimating and sometimes overestimating the real renal function with important medical consequences.